Structural framework of the Wagad uplift and adjoining regions, Kutch rift basin, India, from aeromagnetic data - Radhika, P.R.; Anand, S.P.; Mita, Rajaram; Rao, P. Rama (My University, 2019)
The Kutch sedimentary basin formed during the Late Triassic breakup of Gondwanaland is characterised by horst and graben structures consisting of several east–west trending uplifts surrounded by low-lying plains. The eastern part of the basin has a diverse landscape comprising the Wagad uplift, Banni plain, Island Belt uplift and the Rann of Kutch. This area is bounded by major faults like the South Wagad Fault (SWF), Gedi fault and the Island Belt Fault. The lineaments/faults present in the region at different depth levels and the propagation of these features through the different sedimentary layers are studied using the semi-detailed aeromagnetic data collected over the basin. The aeromagnetic anomaly map depicts several major E–W, NE–SW and NW–SE oriented lineaments/faults, which probably represent structural trends associated with different stages of evolution of this rift basin. Power spectral analysis of the differential reduced to pole magnetic data indicates the presence of four magnetic interfaces. The slopes identified from the 1D power spectra were used for designing matched bandpass filters for isolating and enhancing the magnetic signatures present within those interfaces. Different edge detection techniques were used to delineate the magnetic contacts/faults/lineaments present in those interfaces. In addition, we have computed the radially averaged power spectrum of 121 subset grids each with a dimension of 20 km × 20 km from which three magnetic interfaces were delineated and compared with the stratigraphic sequence of the Wagad uplift and adjoining regions. A major NE–SW fault is delineated from this analysis and suggests that this fault has depth persistence as it dislocates the different magnetic interfaces. Integration with stratigraphic data suggests that this fault was formed prior to the deposition of Miocene Kharinadi formation. We have interpreted that this fault, forming the eastern limit of the Banni basin, might have formed during the passage of the Indian plate over the Reunion hotspot. Based on the results of the aeromagnetic data analysis and other published data, we propose a generalised evolutionary model for the study region.
Keywords: Power spectrum; Aeromagnetic; Wagad uplift; Depth to basement; Lineament mapping